Kearifan Lokal dalam Perspektif Hukum Lingkungan - Marhaeni Ria Siombo (Jurnal Hukum IUS QUIA IUSTUM, 2011)
The research purposively is to examine how the government actualizes the local wisdom that has been rooted in community –thus turning into a law that should be obeyed to overcome the human behavior to wisely act and behave in utilizing the natural resource. This is a research using a judicial-normative method that is descriptively conducted in which the primary data is gained through a direct observation supported by the interview to obtain information. In this research, it can be concluded that from the clave of Lore Lindu, there have been a behavioral principles categorized as “Local Wisdom” or “Indigenous Knowledge” that has not been actualized to strengthen both the regulations and the other wisdom in preventing and minimizing the infraction cases resulting in the damage in National Park Lore Lindu. The local government in this case has not been capable of utilizing the local wisdom of the community in strengthening the policy of the local government to maintain and strengthen the supporting areas in national Park Lore Lindu that in the future could save this area from natural disaster.